Developing Speaking Skill: Barriers Faced by the Bangladeshi EFL Learners - Md. Mohsin Mridha; Sheikh Md. Muniruzzaman (Englisia: Journal of Language, Education, and Humanities, 2020)
This study aims at investigating the prevailing barriers for developing English speaking skill faced by the undergraduate students in Bangladesh. The attempt was to locate the importance of speaking proficiency in English as one of the basic skills of a language in this “English” era. In this global age, the use of English has been inevitable and more often we cannot but use English in different phases of our life. But Bangladeshi EFL learners often fail to attain proper speaking proficiency for some reasons. The reasons behind the incompetence in speaking skill are many and some of them are the influence of mother tongue, lack of vocabulary, lack of practice, unfavorable environment, teachers’ non-cooperation, shyness, fear, language ‘fossilization’ etc. Moreover, students do not get the opportunity to develop English speaking skill in a ‘natural’ environment. The nature of the study is quantitative and the data collection tool is a questionnaire. This paper pinpoints all those problems and presents plausible recommendations in order for developing English speaking skill.